Synthesis, characterization and cytotoxic activity of betulinic acid glucosides against human myeloid leukemia and human T-4 lymphoblastoid cell lines / Mohd Tajudin Mohd Ali and Nurhana Faujan - Mohd Ali, Mohd Tajudin; Faujan, Nurhana (2016)
Glycosylation of betulinic acid with B-D-glucose-pentaacetate was successfully synthesized in the presence of boron trifluoro etherate (BF3.Et2O) in pyridine to give betulinic acid bisglucoside in 92.8% yield. Further treatment of bisglucosides with methanol and sodium metal produced high polarity betulinic acid glucoside with 45% yield. Evaluation of human myeloid leukemia cell (HL60) and human T4-lymphoblastoid cell (CEMSS) activities with both synthesized compounds revealed that both compounds were less potent compared to betulinic acid itself but their water solubility were slightly increase.